A Comparative Analysis of Microbe-Based Technologies Developed at ICAR-NBAIM Against Erysiphe necator Causing Powdery Mildew Disease in Grapes (Vitis vinifera L.) - Malviya, Deepti; Thosar, Ratna; Kokare, Namrata; Pawar, Shital; Singh, Udai B.; Saha, Sujoy; Rai, Jai P.; Singh, Harsh V.; Somkuwar, R. G.; Saxena, Anil K. (Frontiers in Microbiology, 2022)
Globally, Erysiphe necator causing powdery mildew disease in grapevine (Vitis vinifera L.) is the second most important endemic disease causes huge economic losses every year. Till date, management of powdery mildew in grapes is largely dependent upon the use of chemical fungicides. Grape is being considered as one of the high pesticide-demanding crops. Looking at the residual impact of toxic chemical pesticides on environment, animal and human health, microbe-based strategies for control of powdery mildew is an emerging technique. It offers environment-friendly, residue-free and an effective yet safer approach to control powdery mildew disease in grapes. Hence, the aim of the present study was to evaluate the microbe-based technologies, i.e. Eco-pesticide®, Bio-Pulse® and Bio-Care 24® developed at PMI&RB Lab, ICAR-NBAIM, against grape powdery mildew and to integrate these technologies with sulfur to achieve the better disease control under organic systems of viticulture. The experiments were conducted at four different locations, viz. ICAR-NRCG, MRDBS, and two farmers’ fields at Narayangaon and Junnar in Pune district of Maharashtra. Significantly lower disease index was recorded on the leaves of grape plants treated with Eco-Pesticide®/sulfur (22.37) followed by Bio-Pulse®/sulfur and Bio-Care 24®/sulfur at NRCG. A similar trend was observed with the lowest PDI on bunches of Eco-pesticide®/sulfur treated plants followed by Bio-Pulse®/sulfur and Bio-Care®/sulfur. The application of microbial inoculants singly or in combination with sulfur has significant positive impact on the qualitative parameters like pH, total soluble solids, acidity, berry diameter and berry length of the grapes at different locations. Among all the treatments, Bio-Pulse®/sulfur treatment showed the highest yield per vine which was on par with the treatment Eco-Pesticide®/sulfur. When compared with the yield obtained from the untreated control, 2.5 to 3 times more yield was recorded in the plants treated with either of the biopesticides used in combination of sulfur. Even in the case of individual inoculation, the yield per vine was approximately two times higher than the untreated control and water-treated plants across the test locations. Results suggested that microbial technologies not only protect grapevine from powdery mildew but also enhance the quality parameters with increased yield across the test locations.